The Effectiveness Of Using Small Group Discussion On Student’s Speaking Skill Of Recount Text ( A Quasi-Experimental Study at MTS Raudlatul Islam Probolinggo ) - Anis Yuli; Abu Yazid Adhnan Quthni; Ririn Fatmawati (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The purpose of this study was: to measure the effect of using small group discussion on students speaking skill of recount text.The researcher used quantitative approach with quasi-experimental design. The population of the study were the second-grade students of Mts Raudlatul Islam krucil. The researcher used clustering sampling and took two classes; they were speaking class A as control class and speaking class B as experimental class. Before doing the treatment, the students in experimental class were given the pretest. Then, the students taught by using small group discussion technique. At the end of the treatment, the students were given a posttest. To examine the hypothesis, SPSS is used to analyse the data. the researcher applied Post Hoc Test to answer the research problem, and the result showed that (a) speaking skill of experimental class showed the significant value (0.00 < 0.05), it means that there was significant effect of small group discussion toward students? spaking skill of recount text. there was no different effect between speaking skill and speaking anxiety, the use of small group discussion were effective on students? speaking skill and speaking anxiety. It was based on calculation showed that the significant value was higher than alpha (0.810 > 0.05).